PARENTAL ROLES IN SHAPING CHILDREN'S EMOTIONAL INTELLIGENCE AMID SOCIOCULTURAL CHANGE: A QUALITATIVE STUDY OF MUSLIM FAMILIES IN NAGORI BAH JAMBI III - Anggana, Muhammad Irvan; Sahputra, Dika (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The accelerating pace of sociocultural change, particularly driven by rapid technological advancement, presents distinctive challenges to children's emotional development within Muslim family contexts. This study examines the role of parents in shaping children's emotional intelligence (kecerdasan emosi) amid sociocultural change, with a focus on Muslim families in Nagori Bah Jambi III. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation involving three research informants — two parents and one adolescent child — selected through purposive sampling. Data analysis followed the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing, with validity ensured through source triangulation. The findings reveal that parental roles in shaping children's emotional intelligence manifest through five primary dimensions: as guides (pembimbing), motivators, facilitators, supervisors, and moral exemplars (suri teladan). Parents accompany their children in a calm and dialogic manner, provide emotional support during moments of difficulty or failure, create a conducive home environment, supervise gadget use communicatively, and instil social and cultural values through personal exemplarity rooted in Islamic ethics. The study concludes that parental presence is indispensable in cultivating children's emotional intelligence, as it contributes significantly to the development of self-awareness, self-regulation, empathy, and social skills amid the dynamics of sociocultural change. The findings offer practical implications for Muslim families, educators, and policymakers in designing adaptive and values-based parenting approaches in the digital era.